Distribusi Produk Menggunakan Metode Travelling Salesman Problem (TSP) Dengan Konsep Algoritma Heuristik - Yendrizal, Y (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Searching for solutions in determining the shortest route in product distribution is often found in everyday life. Solutions to solve problems can be designed in the form of diagrams consisting of lines and central points. Examples include finding the shortest route (Traveling salesman problem (TSP). The concept of the Traveling Salesman Problem (TSP) is a classic problem of finding the shortest route that a salesman can take when want to visit several cities without having to visit the same city more than once. The problem that often occurs is that the delivery of goods must be on time to the destination, however, because the locations to be addressed are so many and spread across each region, it makes it very difficult for distributors to deliver. goods according to the specified time, the research objective is expected to be able to help distributors in finding the smallest route for delivering goods both in terms of time and saving gasoline, providing distribution route solution options that can minimize delays in goods delivery and optimize human resource transportation facilities. The Heuristic Algorithm produces the best solution to problems which are part of a more complex problem where delivery of orders from distributors to consumers is maximized. The final result of the TSP process is 240 CBDA=240. This method can help in finding the smallest route solution in distributing goods so that it can be used as a reference to get the best results